(untitled) (Patan Pragya, 2021)
The COVID-19 pandemic has forced the closure of educational institutions worldwide. The study reports the students’ perception of online learning during the COVID-19 pandemic. The research was constructed using a descriptive research design. Data were obtained from the 225 students of Tribhuvan University, Kathmandu University, Purbanchal University, Pokhara University, and RajarshiJanak University through simple random sampling techniques and entered into SPSS version 20 for the analysis. The result revealed that online learning was less effective than physical learning. The majority of respondents, 69% a teach university, state that online learning was less effective than physical learning. In contrast, 19% believe it was more successful, and 12% believe it was the same. It is probably due to a lack of genuine engagement and feelings of isolation that impeded online learning. However, M. Phil. and Ph.D. students were enthused about online learning. They considered online learning to be precious. It also found that students at Kathmandu University felt online learning was beneficial. Several elements, including teachers, students, management, and government legislation, influence online learning success, particularly pandemics.